The hangman's beautiful daughter - McCrumb, Sharyn, 1948- (New York : Penguin, 1992)
Laura Bruce, wife of a minister in Appalachia, experiences danger after she is asked by the sheriff to help tend two children who survived a murder-suicide at their family farm.
"An Onyx book.".
Booklist.
Publisher's Weekly.
Wilson's Fiction.
Young Adult
Keywords: Families -- Fiction; Mystery fiction; Appalachian Region -- Fiction; Appalachian Region -- Fiction; Detective and mystery stories